Multi-Objective Optimisation of Woven Composite Draping using Genetic Algorithms. - Skordos, Alexandros A.; Sutcliffe, Michael P. F.; Klintworth, J. W.; Adolfsson, P. (Cranfield University, 2006)
This paper presents a draping optimisation scheme based on the integration of a commercial kinematic drape simulation code and a genetic algorithm. The kinematic model allows a fast solution to the drape model which reproduces successfully the distribution of shear over the component surface, while a genetic algorithm drives the optimisation. Various setups of the problem are considered, including single and multiple objective solutions. The efficiency of the methodology is evaluated based on the results of the scheme applied to the draping of a composite pilot helmet.